(untitled) (Global Journal of Science Frontier Research, 2018)
The authors establish a set of presumably new results, which provide of power series. So in this paper the author try to evaluate Fourier transform of some challenging functions by expressing them as a sum of Fourier transform of functions that diff using definition of Fourier transformations.